2011
DOI: 10.4236/fns.2011.29136
|View full text |Cite
|
Sign up to set email alerts
|

Determinates That Influence Food Comsumption among Older Members of a Midwest Community

Abstract: The goal of this study was to record Muncie, Indiana residents’ change in eating habits over time. Objectives: 1) Identify key determinants that influence a change in participants’ eating habits; 2) Analyze the data for convergent themes among participants and draw patterns; and 3) Compare patterns found in this study population with existing literature and/or accepted theories within the field. Hypotheses on changes in food patterns included: 1) Socio-economic status in the middle-class population maintained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Interestingly, the junior professionals tend to be more price-conscious than the senior ISSN: 2414-309X DOI: 10.20474/jabs-3.5.2 professionals. Pucciarelli & Thomas (2011) underscored that as consumers expand careers and combine incomes, purchasing power for food becomes greater, thus increasing foods bought from all food categories.…”
Section: Results and Discussion Pro Ile Of Buffet Restaurant Consumermentioning
confidence: 99%
“…Interestingly, the junior professionals tend to be more price-conscious than the senior ISSN: 2414-309X DOI: 10.20474/jabs-3.5.2 professionals. Pucciarelli & Thomas (2011) underscored that as consumers expand careers and combine incomes, purchasing power for food becomes greater, thus increasing foods bought from all food categories.…”
Section: Results and Discussion Pro Ile Of Buffet Restaurant Consumermentioning
confidence: 99%
“…It is also possible that cohort differences in expectations and priorities are evident when we examine family meal frequency among adults without children in the household. Many young adults report time constraints for preparing and eating meals (30,31) , whereas among older adults, family mealtime experiences from earlier in their lives may influence current behaviour (32,33) . It is unclear how living with minor children affects these or other aspects of the family dynamic to produce the more stable frequency of family meals across age groups we observed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the elderly readily modify their food habits and are willing to fight the urge of eating their favourite foods as instructed by their doctors (Shanks et al, 2016). This has been categorised as internal indicators that shape the food choice of older people (Pucciarelli & Thomas, 2011). The lowering of fat and cholesterol intake with healthier food choices in order to meet health goals were among the changes specifically made by the elderly (Delaney & McCarthy, 2011;Pucciarelli & Thomas, 2011;Host et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This has been categorised as internal indicators that shape the food choice of older people (Pucciarelli & Thomas, 2011). The lowering of fat and cholesterol intake with healthier food choices in order to meet health goals were among the changes specifically made by the elderly (Delaney & McCarthy, 2011;Pucciarelli & Thomas, 2011;Host et al, 2016). A significant association was found between vegetable intake of different varieties and the higher importance given to health benefits (Appleton et al, 2017) as the elderly assumed that fruits and vegetables were important parts of a healthy diet (Brownie & Coutts, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation